The Bauschinger Effect in Structural Aluminum Alloys - J. Grabowski (Engineering Transactions)
The paper presents test results for the Bauschinger effect on various structural aluminum alloys (PA7N, PA4N, PA2N). The experiments were carried out for the raw materiał, obtained directly from the factory. The rango of initial overstrain ew was 0.2 - 9%. The results of the tests were computed according to two of the most common approaches regarding the defining of the Bauschioger effect. Large differences between both approaches were observed. The experiments proved that the Bauschinger effect for a structural metal may have a diverse character. Essential differences may not only occur in various kinds of materiał but also within the same alloy.